Funny girl : funniest. stories. ever. - Bird, Betsy; Yeager, Delaney, 1990-; Yeager, Mackenzie, 1987-; Telgemeier, Raina; DeCamp, Alison; Vernon, Ursula; Deedy, Carmen Agra; Underwood, Deborah; Bell, Cece; DiPucchio, Kelly; Hughes, Akilah, 1989-; Williams-Garcia, Rita; et al. (Viking, an imprint of Penguin Random House LLC, 2017)
Presents a collection of humorous stories from over two dozen contemporary female writers, as well as autobiographical essays, comics, poems, and comic strips.